The use of specular, polarized neutron reflectivity to determine magnetic density profiles - Barford, W (2003)
The Born and distorted wave Born approximations are used to derive expressions for the specular, reflected intensity of polarized neutrons from magnetic surfaces. Both of these approximations are expected to provide qualitative information on the in-plane magnetic structures. In particular, the spin-flipped component is proportional to the Fourier transform of the in-plane transverse magnetization, while the parallel-spin component is proportional to the Fourier transform of the sum of the in-plane longitudinal magnetization and the nonmagnetic scattering density. The distorted wave Born approximation is more valid near to a critical edge than the Born approximation. Within the distorted wave Born approximation the reflected parallel intensity can also be directly inverted to obtain the sum of the nonmagnetic and in-plane longitudinal magnetization. However, this approximation fails beyond a first-order perturbation in the potential, signified by the violation of flux conservation.